Studying the Effect of Light Incidence Angle on Photoelectric Parameters of Solar Cells by Simulation - Gulomov, Jasurbek; Aliev, Rayimjon; Mirzaalimov, Avazbek; Mirzaalimov, Navruzbek; Kakhkhorov, Jamshidbek; Rashidov, Bobur; Temirov, Sodikjon (International Journal of Renewable Energy Development, 2021)
It is crucial to examine the dependence of photoelectric parameters of solar cells on the light incidence angle. In the present study, two solar cell models have been developed using the Sentaurus Technology Computer-Aided Design software package. The light spectrum AM1.5 has been directed on the frontal surface of solar cells at different angles. It has been found that the angular coefficient of the photoelectric parameters of a solar cell with nanoparticles included, is two times more than that of a simple solar cell. Besides, it has been found that the efficiency of platinum nanoparticles induced solar cells is 2.15 times greater than simple solar cell efficiency. When the light incidence angle has been varied from 0 to 60 degrees, the short-circuit current has changed by 11% for simple solar cells and by 10% for solar cells with nanoparticles. Further, it has been observed that the variation of power for simple solar cells is 12.5%, while it is 10.5% for solar cells with nanoparticles. In addition, the short-circuit current of solar cells with nanoparticles has been found to be linear within a light incidence angle ranging from 0 to 60 degrees.